The agricultural frontier in the areas surrounding the Terraba Sierpe Nacional Wetland and its implications for the sustainability of production systems - Montero Solís, Nathaly (2020)
The geographical areas of the South Pacific of Costa Rica agglomerate one of the most important natural elements in the Valle del Diquis region. The Térraba-Sierpe National Wetland (TSNW) represents a relevant area for global biodiversity, but agricultural activities have endangered its sustainability over time. The objective of this research is to update the land use of areas surrounding the HNTS, in order to analyze the situation of the agricultural frontier and its implications for the wetland sustainability, using remote sensing techniques, field trips, bibliographic review and electronic tools like DNR Garmin and Arc Gis 10.